Maternal Supplementation of Vitamin E or Its Combination with Hydroxytyrosol Increases the Gut Health and Short Chain Fatty Acids of Piglets at Weaning - Hernan D. Laviano; Gerardo Gómez; Rosa Escudero; Yolanda Nuñez; Juan M. García-Casco; María Muñoz; Ana Heras-Molina; Clemente López-Bote; Antonio González-Bulnes; Cristina Óvilo; Ana I. Rey (MDPI AG, 2023)
An adequate intestinal environment before weaning may contribute to diarrhea predisposition and piglet development. This study evaluates how the dietary supplementation of vitamin E (VE) (100 mg/kg), hydroxytyrosol (HXT) (1.5 mg/kg) or the combined administration (VE + HXT) given to Iberian sows from gestation affects the piglet's faecal characteristics, short chain fatty acids (SCFAs), fatty acid profile or intestinal morphology as indicators of gut health; and quantify the contribution of the oxidative status and colostrum/milk composition to the piglet's SCFAs content and intestinal health. Dietary VE increased isobutyric acid (iC4), butyric acid (C4), isovaleric acid (iC5), and ∑SCFAs, whereas HXT increased iC4 and tended to decrease ∑SCFAs of faeces. Piglets from HXT-supplemented sows also tended to have higher faecal C20:4n-6/C20:2 ratio C22:6 proportion and showed lower occludin gene expression in the duodenum. The combination of both antioxidants had a positive effect on iC4 and iC5 levels. Correlation analyses and regression equations indicate that faecal SCFAs were related to oxidative status (mainly plasma VE) and colostrum and milk composition (mainly C20:2, C20:3, C20:4 n-6). This study would confirm the superiority of VE over HXT supplementation to improve intestinal homeostasis, gut health, and, consequently piglet growth.